Strategi Dakwah Pimpinan Cabang Muhammadiyah Dalam Mengurangi Penyalahgunaan Narkoba : Di Kalangan Pemuda Kecamatan Medan Tembung Kota Medan - Veni Aqilla Rizki; Hasrat Efendi Samosir (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
The study aims to determine the strategies, activities, and obstacles in implementing the da'wah program at the Muhammadiyah Branch Leadership where Muhammadiyah is located in Mandala. This study uses a descriptive qualitative research method using observation, interview, and documentation techniques in collecting data. Based on the results of the study, it was found that by implementing a good da'wah strategy at the Muhammadiyah Branch Leadership. The Muhammadiyah Leadership implements a da'wah strategy by involving young people to reduce or prevent drugs, including the maghrib program to study the Koran every Monday to Thursday, every Sunday holding youth studies, once a month there is a mabit activity (night of fostering faith and piety). The Muhammadiyah Branch Leadership tries to provide education on the dangers of drug abuse for young people.